2021
DOI: 10.3390/jpm11050357
|View full text |Cite
|
Sign up to set email alerts
|

Transient Response of Olaparib on Pulmonary Artery Sarcoma Harboring Multiple Homologous Recombinant Repair Gene Alterations

Abstract: Primary pulmonary artery sarcoma (PPAS) is a rare malignancy arising from mesenchymal pulmonary artery cells and mimics pulmonary embolism. Palliative chemotherapy such as anthracycline- or ifosfamide-based regimens and targeted therapy are the only options. However, the evidence of clinically beneficial systemic treatment is scarce. Here, we report a case of disseminated PPAS achieving clinical tumor response to olaparib based on comprehensive genetic profiling (CGP) showing genetic alterations involving DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Moreover, Paclitaxel has been shown to be effective ( 18 , 21 ), especially in patients prone to developing pulmonary artery hypertension. Recent advancements in anticancer therapies have led to the exploration of vascular-targeting agents like apatinib, anlotinib, and PD-1/PD-L1 immunotherapies in treating PAS, with promising results reported in several studies ( 22 ). Nonetheless, a standardized chemotherapy or targeted treatment protocol for PAS has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Paclitaxel has been shown to be effective ( 18 , 21 ), especially in patients prone to developing pulmonary artery hypertension. Recent advancements in anticancer therapies have led to the exploration of vascular-targeting agents like apatinib, anlotinib, and PD-1/PD-L1 immunotherapies in treating PAS, with promising results reported in several studies ( 22 ). Nonetheless, a standardized chemotherapy or targeted treatment protocol for PAS has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…They hypothesized that owing to the clonal heterogeneity of the tumor and the potential contribution of PDGFRA and EGFR signaling pathways, imatinib did not provide disease control and concluded that the therapeutic activity of this targeted agent in PAIS cannot be determined based on their findings [3]. In a report of a metastatic patient with genetic profiling showing alterations in the DNA repair pathway, olaparib achieved transient disease control for 2 months [20].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not surprising that CGP is increasingly being used in the evaluation and management of sarcomas ( 12 ). For instance, Wu et al ( 13 ) reported a case of disseminated primary pulmonary artery sarcoma achieving clinical tumor response to olaparib based on genetic alterations detected by CGP, which involved the DNA repair pathway. This provides supportive evidence that olaparib may be a promising therapeutic agent for patients with disseminated primary pulmonary artery sarcoma harboring haploinsufficiency of the DNA damage repair mechanism ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Wu et al ( 13 ) reported a case of disseminated primary pulmonary artery sarcoma achieving clinical tumor response to olaparib based on genetic alterations detected by CGP, which involved the DNA repair pathway. This provides supportive evidence that olaparib may be a promising therapeutic agent for patients with disseminated primary pulmonary artery sarcoma harboring haploinsufficiency of the DNA damage repair mechanism ( 13 ). Although CGP may refine the histological tumor diagnosis with its inherent ramifications for management, little is known regarding its application in PAIS.…”
Section: Discussionmentioning
confidence: 99%